The Relationship of Personal Hygiene to the Incidence of Thypus Abdominalis - Arsyad, Lenni (Omni Health Journal, 2025)
Background: Health development is a key indicator of national progress and is influenced by several determinants, including environment, behavior, health services, and heredity. Personal hygiene is one behavioral factor that significantly contributes to the prevention of infectious diseases such as typhus abdominalis. Objective: This study aimed to determine the relationship between personal hygiene and the incidence of typhus abdominalis. Methods: A cross-sectional study was conducted using a total sampling technique involving 45 respondents in the working area of the Rumbia Health Center, Jeneponto Regency. Data were collected through validated questionnaires and analyzed using the chi-square test. Results: There was a statistically significant and strong relationship between hand hygiene before eating and the incidence of typhus abdominalis (p < 0.001). A moderate relationship was found between drinking water cleanliness and typhus incidence (p = 0.02), and a strong relationship was identified for food hygiene (p < 0.001). Additionally, there was a moderate relationship between the cleanliness of latrine use and disease incidence (p = 0.03). Conclusion: Personal hygiene practices, particularly handwashing, food hygiene, and latrine use, are associated with the incidence of typhus abdominalis. Public health efforts should focus on improving sanitation facilities and promoting hygienic behaviors to reduce disease transmission.